Analysis of international scientific production on climate change and air pollution (Research, Society and Development, 2020)
Much has been written about climate change and the effects caused by human activities on the environment. Researches related to the topic increases rapidly and is present in content search networks at a relevant level, since this has been a relevant theme since the 1970´s. In this context, this research was carried out with the aim of evaluating the progress of scientific research in the over the years on the themes of climate change and air pollution based on publications on the topics in the database of the Web of Science, selecting a broad scientific- international academic history, in the period of 49 years (1971 to 2020) - following the following criteria: web areas, publications - journals / periodicals, country, occurrence, authors and terms. With the information, it was possible to generate a mapping in which the breadth of theme is visible in publications the last decades in the world. Brazil does not stand out among the countries that most publish on the subject. The increase in academic production has been predominantly observed in authors from other countries, such as the United States, China, England, Italy, Germany, among others. The peak of publications was registered in the year 2018, with a decrease in 2019 and 2020, being able to observe the scope of the theme associated with concerns related to global problems caused to the environment, in addition to socioeconomic damage. The greater occurrence in citations demonstrates that there is a collaborative interconnection between groups of authors who frequently research the topic, promoting the dissemination of information and knowledge.